Puberty in pre‐Roman times: A bioarchaeological study of Etruscan‐Samnite adolescents from Pontecagnano (southern Italy). (30th June 2022) - Bareggi, Alessia; Pellegrino, Carmine; Giuffra, Valentina; Riccomi, Giulia
Abstract: Objectives: Puberty is a crucial part of life, representing the biological transition from childhood to adulthood. With the aim of expanding current knowledge of pubertal development and the life course in past populations, this study provides the first investigation of puberty in pre‐Roman Italy. Materials and methods: Nine skeletal and dental puberty indicators were assessed in a sample of 84 Etruscan and Samnite individuals (8.0–23.9 years) from Pontecagnano (southern Italy, seventh–fourth centuries BC) to garner insights into the timing and duration of different pubertal stages. Results: Adolescents from Pontecagnano entered puberty at 10–12 years and completed pubertal development at approximately 20–21 years. Menarche occurred between 14 and 17 years. Remarkable variability in pubertal timing and an overall prolonged pubertal tempo were observed. Unexpectedly, females completed puberty at the same age as males. Discussion: The onset and completion of puberty in Pontecagnano are mostly in line with pubertal trends emerging from other bioarchaeological studies and historical sources. The considerable inter‐individual variability in pubertal timing seen at the site probably reflects its great sociocultural heterogeneity, whilst the prolonged pubertal tempo could represent an adaptive mechanism in response to environmental disruptors. These may have included endemic diseases characteristic of Pontecagnano's marshy environment and pollutants produced by the Etruscan and Samnite metallurgical industries. Moreover, the role of catch‐up growth in favouring better pregnancy outcomes could explain why female puberty appears particularly stretched. The importance of exploring pubertal development in past societies without culturally biased assumptions is emphasised.